Experimental models for contamination of titanium surfaces and disinfection protocols. Issue 10 (10th February 2016) - Sousa, Vanessa; Mardas, Nikos; Spratt, David; Boniface, David; Dard, Michel; Donos, Nikolaos
Abstract: Aim: The aim of this pilot study was to describe an in vitro model of peri‐implantitis microcosm for contamination of titanium surfaces and an in vivo model for evaluating different disinfection strategies of titanium surfaces. Materials and methods: Biofilms were grown in vitro for 30 days on sandblasted large‐grit acid‐etched (SLA) Ti discs ( n   =  69) in a constant depth film fermentor (CDFF) associated with peri‐implantitis conditions. Four Swedish loop rabbits were randomly allocated in three test groups (T1, T2, T3 ) and one control group (C). In group C, two sterile SLA Ti discs were implanted/fixed in each tibia. In the test groups (to evaluate the potential of different surface disinfection techniques), one sterile and three previously disinfected SLA Ti discs were placed following different disinfection protocols: group T1 : the discs were treated with a titanium brush – TiB; group T2 : the discs were treated with the combination of TiB and photodynamic therapy; and group T3 : the discs were treated with TiB and 1%NaOCl plus 0.2%CHX. Tensile strength test and qualitative histological analysis were performed on all 16 discs after 4 weeks of healing. Results: Thirty days following CDFF emulating peri‐implantitis microcosm, all SLA Ti discs had a mean total viable aerobes and facultative anaerobes count of 8.06 log10  CFU/biofilm and anaerobes 8.32 log10  CFU/biofilm. Before implantation/fixation on the tibia, differences of log10  CFU/biofilm counts between control and test groups after post hoc adjustment were highly significant ( P  < 0.001). In the in vivo analysis, group C exhibited the highest tensile strength (67.60 N [25.64–127.02]) and the histological sections revealed the presence of dense mature bone in direct contact with the disc surface. The analysis at the test groups showed that T2 presented with the highest tensile strength in comparison with the other two test groups. Conclusions: The in vitro model used in this study provides a valuable and reproducible tool for evaluating the in vitro dynamics of the peri‐implantitis microcosm biofilm and for contaminating in a reproducible manner titanium surfaces. At the same time, the in vivo model used in this study provides a standardised mode of evaluating disinfection modalities of previously infected titanium surfaces.